2012
DOI: 10.18043/ncm.73.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Academic Performance of North Carolina College Students

Abstract: background Depression negatively affects cognitive functioning and, consequently, academic performance. Studies of this association have yielded conflicting results and have not fully considered other factors that may play a role in academic performance. This study examines the relation between depression and academic performance in students at a large urban university in North Carolina. methods We analyzed data from student responses to the 2008 cross-sectional National College Health Assessment to create cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…In literature, various studies have conflicting findings regarding the association of depression and academic performance of students. A study that was conducted on North Carolina College students indicates that depression and academic performance have strong and negative association and supports our study finding that depression leads to poor academic performance among students while another study with conflicting finding that was carried out among Medical students of Islamabad Pakistan, shows that depression and academic performance have no association and depression does not change the academic performance of students [16], [17]. In the presence of findings in literature regarding the association of depression and academic performance, that supports our study results, we encourage the idea that by reducing depression we may be able to improve the academic performance of students.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In literature, various studies have conflicting findings regarding the association of depression and academic performance of students. A study that was conducted on North Carolina College students indicates that depression and academic performance have strong and negative association and supports our study finding that depression leads to poor academic performance among students while another study with conflicting finding that was carried out among Medical students of Islamabad Pakistan, shows that depression and academic performance have no association and depression does not change the academic performance of students [16], [17]. In the presence of findings in literature regarding the association of depression and academic performance, that supports our study results, we encourage the idea that by reducing depression we may be able to improve the academic performance of students.…”
Section: Discussionsupporting
confidence: 86%
“…Along with different psychological difficulties because of depression that are mentioned above, depression is also associated with adverse impact on mental functioning and hence consequently it can also influence academic performance [15]- [16]. In literature, different studies have conflicting findings regarding the association between depression and academic performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature, it has been shown that depression influences the way individual eats, sleeps, and behaves [13]. Furthermore, a study has also indicated that depression brings other psychological issues in lives including stress, burnout, tension, suicidal thoughts, substance abuse and impairment in cognitive functions and these psychological issues can affect the performance of students in academics and other aspects of life [14], [15]. However, it has been shown that medical students can learn to adapt by using various coping strategies like positive thinking, meeting friends, discussing it with their parent or guardian, seeking medical advice, consulting a religious person, consuming food, sleeping, using relaxation techniques, playing music, crafting, outdoor activities, consuming media, drinking or consuming other legal or illicit drugs [12], [16], [17].…”
mentioning
confidence: 99%